The Effect of Combination of Oleander Leaf Extract (Nerium oleander L.) With Neem Leaf (Azadiracta indica A. Juss) on Mortality Golden Snail (Pomaceae canaliculata L.) - Supriatno Supriatno; Nur Asiah; Asiah Asiah M D; Djufri Djufri; Safrida Safrida (Jurnal Penelitian Pendidikan IPA, 2023)
The golden snail is a pest that causes crop failure in rice plants. Farmers control the golden snail by using pesticides, which can have a negative impact on the environment, so another alternative is needed that can control the golden snail, namely vegetable pesticides. This study aims to determine the effect of a combination of oleander leaf extract and neem leaves on the mortality of Keong Mas. The method used in this research is the experimental method with a factorial completely randomised design (CRD). The study consisted of 2 factors, namely factor N (Oleander leaf) and factor A (Azadiracta indica leaf), each of which had 4 levels, so there were 16 treatment combinations and 3 replications. There were 480 golden snails in the study. After 12 hours of observation, the N3A3 treatment tested by ANOVA showed significantly different results (fcount > ftable = 66.00 > 2.01) and caused 30 test animals to die with a mortality rate of 77%. Â The conclusion from this study is that the combination of oleander leaf extract with neem leaves greatly influences the mortality of the golden snail